2013
DOI: 10.1371/journal.pone.0059707
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Online Platform for Multiple Sclerosis Research: Patient Description, Validation of Severity Scale, and Exploration of BMI Effects on Disease Course

Abstract: ObjectivesTo assess the potential of an online platform, PatientsLikeMe.com (PLM), for research in multiple sclerosis (MS). An investigation of the role of body mass index (BMI) on MS disease course was conducted to illustrate the utility of the platform.MethodsFirst, we compared the demographic characteristics of subjects from PLM and from a regional MS center. Second, we validated PLM’s patient-reported outcome measure (MS Rating Scale, MSRS) against standard physician-rated tools. Finally, we analyzed the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 40 publications
2
59
1
Order By: Relevance
“…On the other hand there is increasing evidence that this kind of "uncontrolled" data may have a similar quality and may be used for research as those generated in "classical" studies. (Bove et al 2013). We do not see a clear expected direction for a bias in the transition phase.…”
Section: Discussioncontrasting
confidence: 61%
“…On the other hand there is increasing evidence that this kind of "uncontrolled" data may have a similar quality and may be used for research as those generated in "classical" studies. (Bove et al 2013). We do not see a clear expected direction for a bias in the transition phase.…”
Section: Discussioncontrasting
confidence: 61%
“…The MSRS is an instrument that measures functional disability in MS and includes seven items that assess walking, upper limb function, vision, speech, swallowing, thinking/memory/cognition, sensation/burning/pain (Appendix). The properties of the instrument have been validated and published elsewhere [27]. For analyses, we used data from participants that reported MSRS within 30 days of the baseline assessment.…”
Section: Methodsmentioning
confidence: 99%
“…One study showed that families dealing with rare diseases are active in social media communities, 10 and a few reports demonstrate the use of social media to recruit subjects for broad population-based studies, studies of more common diseases, or small studies of less common diseases. [11][12][13][14] To our knowledge, only 1 study has reported using primarily social media in a prospective study of a very rare disease: an online support group of 12 individuals was accessed to obtain consent for a study of spontaneous coronary artery dissection. 15 By contrast, our study demonstrates the feasibility of using social media to reach a significantly larger number of participants via multiple online communities using only online resources.…”
Section: Lessons Learned and Future Possibilitiesmentioning
confidence: 99%